Adsorption of Organic Compounds on Activated Carbon Derived from Peanut Shells. Potential Theory Correlation for Estimating Adsorption Capacities and Affinity Coefficients - Elio E. Gonzo (Adsorption Science & Technology)
Adsorption isotherms of eight organic contaminants (acetone, pyridine, phenol, iodine, Methylene Blue, Congo Red, Reactive Navy and tannic acid) onto an activated carbon obtained from peanut shells have been studied at 22°C. The experimental data were analyzed using the Polanyi Potential Theory and the Dubinin–Astakhov equation and collapsed into one general characteristic curve. This analysis allowed the affinity coefficient for each organic compound to be obtained using phenol as the reference substance. A useful correlation for the calculation of the affinity coefficient as a function of relative parachor is presented.